Early age assessment of cement mortar incorporated high volume fly ash. Issue 1 (March 2021) - Hanoon, Dhoha Saad; Sallal, Ali Kadhim; Shubbar, Ali A.; Al-Khafaji, Zainab S.; Nasr, Mohammed Salah; Al-Mamoori, Shahad F.; Al-Fehaida, Ali; Abdulraheem, Mustafa S.; Abdulzahra, Firas R.; Alkhayyat, Ahmed; Al-Rifaie, Ali; Hashim, Khalid
Abstract: The technique of replacing the cement with other alternative materials focuses on the production of materials with similar performance and reduced environmental impacts relative to traditional cement. The main aim of this study is to investigate the effect of replacing the cement content with high volume of Pulverised Fuel Ash (PFA) on the mechanical performance of cement mortar. Three mixtures were prepared with different percentages of PFA (20%, 40% and 60%) as replacement of cement along with other mixture that made with 100% cement as a control mixture. In order to evaluate the performance of the cement mortars, compressive strength and Ultrasonic Pulse Velocity (UPV) tests after 7, 14 and 28 days of curing was used. The results indicated that for all ages of curing, the increase of PFA contents caused a reduction in the compressive strength and UPV in comparison with the control mixture. After 28 days of curing, the results indicated that the mixture incorporated 20% PFA has similar UPV value relative to the control mixture. Such findings will significantly contribute in reducing the cost of the produced mortar by reducing the amount of used cement and this consequently reduce the cement demands/manufacturing. Less production of cement will reduce the Carbon Dioxide (CO2) emissions of the cement industry.